The Role of School Counselors in Integrating Character Education to Develop the National Graduate Profile in Junior High Schools - Naaria Natasha Mae Johar Irawan; Meiske Yunithree Suparman; Maqdalene Jean Marwin; Josette Eclesiana Elize (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the strategic role of guidance and counseling (BK) teachers in integrating character education to make the National Graduate Profile at the Junior High School (SMP) level, that are aligned with the eight dimensions of Graduate Competency Standards (SKL) under Permendikdasmen Number 10, of 2025. Using a qualitative, descriptive approach, data were collected through semi-structured interviews with three BK teachers from two different junior high schools. The collected data were processed and analyzed using NVivo software. The findings reveal that BK teachers serve multifaceted roles as guides, facilitators, and mentors by transforming negative stigma, utilizing real-case handlings as moral reflection moments, and providing a safe space for students. However in the digital era, there are many obstacles to the implementation, such as student reliance on gadgets that cause instant mentality and lack of self-control, parents and students distant relation and permissive parenting styles, structural limitations like unequal teacher to student ratios, and lack of standardized character evaluation tools. As a result, character internalizations today are still episodic. In order to methodically reach the desired National Graduate Profile, this study emphasizes the requirement for programmatic restructuring, including clear defined job boundaries, official BK hour allocations, interactive module developments, and improved parent-school interactions.